2022
DOI: 10.4081/jphr.2021.2392
|View full text |Cite
|
Sign up to set email alerts
|

The Sustainability of Premium Payment of National Health Insurance's Self-Enrolled Members in Jakarta Greater Area

Abstract: Background: The sustainability of the National Health Insurance (NHI) program heavily relies on the premium of its member. The negligence of a large number of members to pay the premium lead to the failure of the Social Security Agency for Health (SSAH) to deliver its services. This study aims at analyzing important factors that influence the sustainability of premium payment of NHI’s self-enrolled members in the Jakarta Greater Area.Design and MethodS: This study performed an econometric analysis from the pan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…Majority of the participants had some form of certi cates. This is consistent with studies by [13,17] which revealed that majority(more than 60%) and more than a third had graduated from senior high school or more respectively. Likewise, the nding in this study supports another one by [18].…”
Section: Discussionsupporting
confidence: 92%
“…Majority of the participants had some form of certi cates. This is consistent with studies by [13,17] which revealed that majority(more than 60%) and more than a third had graduated from senior high school or more respectively. Likewise, the nding in this study supports another one by [18].…”
Section: Discussionsupporting
confidence: 92%
“…Due to the large number of work accidents, BPJS Employment spent IDR 1.79 trillion to pay claims in 2021. The increase was 14.97% compared to previous years which amounted to IDR 1.56 trillion (Nurhasana et al, 2022).…”
Section: Introductionmentioning
confidence: 76%
“…Higher income among the population increases people's interest and awareness to comply with premium payments (Russell, 1996). Income is a facilitating factor directly influencing individual behavioral changes (Nurhasana et al, 2022). In this context, income is a factor that enables behavioral changes necessary to afford selfpayment of BPJS Kesehatan premiums.…”
Section: Resultsmentioning
confidence: 99%